SCREENING FOR CYSTIC FIBROSIS: THE IMPORTANCE OF USING THE CORRECT TOOLS - Shah, Uzma; Moatter, Tariq (Journal of Ayub Medical College Abbottabad, 2006)
Background: Cystic Fibrosis (CF) is a potentially lethal genetic disorder. The most frequent mutation worldwide in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene is designated as the Delta F508 mutation. This mutation was found in only 33% of Pakistani patients studied. Since the common Pakistani mutations remain to be identified, appropriate screening tools are required to identify disease. Sweat chloride determinations remain the gold standard for diagnosing CF. This study was done to emphasize the importance of using the correct tests. Methods: The study was conducted at the Aga Khan University Hospital. The CFTR delta F508 mutation was tested on blood samples from patients suspected with CF. Sweat chloride analysis using pilocarpine iontopharesis was done with a positive value of greater than 60 meq/L. Results: 57 pediatric samples were screened for the delta F508 mutation and were positive in only 10.6 % of all patients tested. 12/57 (21%) had a preliminary sweat test. 6/12 (50%) of these patients had an abnormal sweat test and 3/6 patients with an abnormal sweat chloride (50 %) had deltaF508 mutations - 2/6 (33%) were homozygotes and 1 was a compound heterozygote. Since 79% did not have a sweat test, it was difficult to assess whether this subset of patients had cystic fibrosis with a CFTR mutation other than the delta F508 tested or no CF. Conclusion: Sweat chloride analysis is critical to distinguish CF from other causes of severe pulmonary and pancreatic insufficiencies and to define patients requiring further analysis. Key words: Cystic fibrosis, sweat chloride, mutation analysis